Fungal-mediated solid-state fermentation ameliorates antinutritional factors but does not improve in vitro digestibility of marama (Tylosema esculentum) beans - Joel Gbenle; Marlin Mert; Nkateko N. Phasha; Molatelo Junior Madibana; Freddy Manyeula; Oluwaseun Peter Bamidele; Rashieda Toefy; Siphosethu Richard Dibakoane; Victor Mlambo (Future Foods)
Beans from the orphan legume Tylosema esculentum (marama plant) have the potential to partially or completely replace soybeans in human and animal diets. However, their high levels of antinutritional factors and low levels of certain essential amino acids may limit this utility. This study aimed to enhance the food/feed value of marama beans through fungal-mediated solid-state fermentation (SSF) using Aspergillus oryzae, Aspergillus sojae, and their co-culture, focusing on the beans' functional and nutritional properties. Contrasts revealed that fermented beans had lower (p < 0.05) acid detergent fiber (ADF), acid detergent lignin (ADL), cellulose, and hemicellulose levels compared to non-fermented beans, while crude fat content was unchanged (p > 0.05). Beans fermented with A. sojae showed higher crude protein (CP) content (p < 0.05) than non-fermented beans. Fermented beans exhibited lower (p < 0.05) phytic acid and trypsin inhibitor activity, but significantly higher (p < 0.05) total phenolic content compared to non-fermented beans. Non-fermented beans had higher (p < 0.05) in vitro enzyme protein digestibility (IVPD) than single-strain-fermented beans. Fungal fermentation increased (p < 0.05) dispersibility and reduced water and oil absorption capacities but did not affect (p > 0.05) pH and bulk density. In conclusion, fungal-mediated SSF reduced some fiber fractions, phytic acid, and trypsin inhibitor activity in marama beans, though this did not result in enhanced simulated protein digestibility.